Effect of Vermicompost and Rice Husk Ash as an Organic Growing Media on Rice Seedling and Mat Quality in Tray Nursery - Widi, Hastungkoro; Zaki, Muhamad Khoiru; Munawaroh, Umi (Research and Social Study Institute, 2025)
Background: Efficient mechanized rice transplanting depends on both the structural integrity of seedling mats and the physiological quality of the seedlings. To address this need, enhancing seedling and mat through organic growing media is essential for optimizing mechanized rice transplanting.Aims & Methods: This study aimed to evaluate the effects of organic amendments on seedling quality (seedling height, biomass, and plant population) and mat characteristics (thickness, weight, rolling score and diameter) in tray nursery. A randomized complete block design with three replications was employed, testing four treatments: alluvial soil without organic amendment (CO), with vermicompost (V), with rice husk ash (R), and with vermicompost and rice husk ash (RV).Results: The results showed that the rice seedling nursery using a mixture of soil and organic growing media (R, RV, and V) produced better seedling quality compared to CO including seedling height, biomass, and plant population. Regarding mat performance, RV produced the thickest (1.77 cm) and lightest (3.27 kg) mats, aligning with ideal conditions for mechanical transplanting. In contrast, CO mats were the heaviest (4.40 kg), and V produced the thinnest mats (1.40 cm). Rolling quality was highest in CO (score 10), while RV mats showed lower rolling integrity (score 6.7). V treatment achieved the smallest roll diameter (13.87 cm), facilitating better handling and transport. Overall, the results demonstrate that organic amendment selection significantly affects both physiological seedling traits and the physical integrity of seedling mats. The RV treatment offered the most balanced improvement in mat structure and seedling growth, making it a promising option for mechanized rice production.